Phenol Abatement by Titanium Dioxide Photocatalysts: Effect of The Graphene Oxide Loading - Naknikham, Usuma (Nanomaterials (Basel), 2019)
Hetero-photocatalytic graphene-TiO(2) materials have, in the literature, been found to possess better photocatalytic activity for environmental applications compared to pure TiO(2). These types of materials can be prepared in different ways; however, their photocatalytic performance and quality are not easily controlled and reproduced. Therefore, we synthetized graphene oxide-TiO(2) nanoparticles by sol-gel reaction from TiCl(4), as precursor, with two different methods of synthesis and with a graphene oxide (GO) loading ranging from 0 to 1.0. This approach led to a good adhesion of GO to TiO(2) through the Ti-O-C bonding, which could enhance the photocatalytic performances of the materials. Overall, 0.05 wt % GO loading gave the highest rate in the photodegradation of phenol under visible light, while higher GO loadings had a negative impact on the photocatalytic performances of the composites. The 0.05 wt % GO-TiO(2) composite material was confirmed to be a promising photocatalyst for water pollutant abatement. The designed synthetic approach could easily be implemented in large-scale production of the GO-TiO(2) coupling materials.